Gottried Mann’s position in the controversy over Kant’s philosophy - Noras, Andrzej J. (Folia Philosophica, 2000)
The subject of the present article is Gottfried Martin’s interpretation of Kant’s philosophy. The significance of this insight into the thought of the Königsberg philosopher consists in its taking the historical context of that thought as much as possible into consideration. Martin’s interpretation is distinguished by its attempt at obtaining a synthetic view on Kant’s philosophy, and, at the same time, at showing it in the context of the development of philosophy as such. Martin, when dealing with the problem of the continuity of philosophy, the problem of transcendentalism, and of the thing-in-itself, does not exclude any interpretation, but only tries to demonstrate their limitations. Thus, in a dispute with other views, an interpretation of Kant’s philosophy that certainly may be regarded as one of the most significant in th the 20th c. philosophy is arrived at.